Anatomical Characterization of the Tear Trough and the Lid-Cheek Junction: An Iodine Staining Technique Based on High-Resolution Micro–Computed Tomography. Issue 4 (3rd February 2022) - Chen, Shuxiu; Ma, Hengyuan; Song, Tao; Li, Haidong; Wu, Di; Wang, Yongqian; Yin, Ningbei
Abstract : Background: The literature presents the tear trough and lid-cheek junction's controversial anatomical explanations. In this study, the authors explored the anatomical characterization of the tear trough deformity and lid-cheek junction. Methods: Twelve human cadaver specimens were obtained from the authors' anatomy department. Iodine staining and high-resolution micro–computed tomography was used to observe the suborbital area's anatomy. Anatomical studies and histologic evaluation were performed. Results: The orbicularis retaining ligament is composed of a main septum right on the rim and multiple fibrous septa in the retro-orbicularis plain. The septum arises from the deep fascia of the palpebral part of the orbicularis oculi at approximately the level of the medial corneoscleral limbus, anchors the muscle to the orbital rim, and continues laterally as the lateral orbital thickening at the lateral canthus. Along the lid-cheek junction, multiple fibrous septa emanating from the deep fascia of the orbital part of the orbicularis oculi converge to the above septum. Using three-dimensional simulation, the skin-insert junction between the pre–palpebral part of the orbicularis oculi and pre–orbicularis oculi fibers precisely corresponded with the tear trough and the lid-cheek groove. Anatomical studies and histologic evaluation confirmed these observations. Conclusions: The orbicularis retaining ligament's subtle anatomical features are clearly seen using the approach described. The tear trough and the lid-cheek junction's anatomical characterization is defined by a suborbital ligament-fascia system whose description has implications in designing lower eyelid cosmetic surgery.